Cardiac safety analysis of first-line chemotherapy drug pegylated liposomal doxorubicin in ovarian cancer - Xin-Ru Li; Xing-Han Cheng; Guo-Nan Zhang; Xiao-Xin Wang; Jian-Ming Huang (Journal of Ovarian Research, 2022)
Abstract Pegylated liposomal doxorubicin (PLD) is a nano-doxorubicin anticancer agent. It was used as early as 2014 to treat ovarian and breast cancer, multiple myeloma and Kaposi's sarcoma. The 2018 National Comprehensive Cancer Network guidelines listed PLD as first-line chemotherapy for ovarian cancer. PLD has significant anticancer efficacy and good tolerance. Although PLD significantly reduces the cardiotoxicity of conventional doxorubicin, its cumulative-dose cardiotoxicity remains a clinical concern. This study summarizes the high-risk factors for PLD-induced cardiotoxicity, clinical dose thresholds, and cardiac function testing modalities. For patients with advanced, refractory, and recurrent malignant tumors, the use of PLD is still one of the most effective strategies in the absence of evidence of high risk such as cardiac dysfunction, and the lifetime treatment dose should be unlimited. Of course, they should also be comprehensively evaluated in combination with the high-risk factors of the patients themselves and indicators of cardiac function. This review can help guide better clinical use of PLD.